Erratum: Ureasilicate hybrid coatings for corrosion protection of galvanized steel in cementitious media - Figueira, R. B. (2015)
Artigo completo publicado na revista "Journal of The Electrochemical Society" 160:10 (2013) 467-479 e disponível no RepositóriUM em: http://hdl.handle.net/1822/33855